Nonlinear active suspension system with backstepping control strategy - Basari, Amat Amir; Md Sam, Yahaya; Hamzah, Norhazimi (2007)
The purpose of this paper is to investigate the performance of a quarter car nonlinear active suspension system with a backstepping control approach. Dynamic model of a suspension system is highly nonlinear. Rotational motion of the sprung mass (car body) and rotational motion of control arm are terms that always be neglected in the linear suspension system. This paper presented a suspension system that admit the rotational motion of the control arm. Backstepping control is a recursive control procedure which breaks a design problem for the full system into a sequence of design problems for lower order systems [1]. It is a kind of robust controller which the matching condition can be relaxed for a class of nonlinear system. Performance of a suspension system is determined by the ride quality and the car handling. These two criteria is examined and presented.